Bariatric Surgery as Potential Treatment for Nonalcoholic Fatty Liver Disease: A Future Treatment by Choice or by Chance? - Shuja Hafeez; Mohamed H. Ahmed (Hindawi Limited, 2013)
Morbid obesity is strongly associated with nonalcoholic fatty liver disease (NAFLD) which is one of the most common causes of chronic liver disease worldwide. The current best treatment of NAFLD and NASH is weight reduction through life style modifications, antiobesity medication, and bariatric surgery. Importantly, bariatric surgery is the best alternative option for weight reduction if lifestyle modifications and pharmacological therapy have not yielded long-term success. Bariatric surgery is an effective treatment option for individuals who are grossly obese and associated with marked decrease in obesity-related morbidity and mortality. The most common performed bariatric surgery is Roux-en-Y gastric bypass (RYGB). The current evidence suggests that bariatric surgery in these patients will decrease the grade of steatosis, hepatic inflammation, and fibrosis. NAFLD per se is not an indication for bariatric surgery. Further research is urgently needed to determine (i) the benefit of bariatric surgery in NAFLD patients at high risk of developing liver cirrhosis (ii) the role of bariatric surgery in modulation of complications of NAFLD like diabetes and cardiovascular disease. The outcomes of the future research will determine whether bariatric surgery will be one of the recommended choice for treatment of the most progressive type of NAFLD.